"Odonata Community Index – Corsica" (OCIC): A new biological index based on adult odonate populations for assessment of the ecological status of watercourses in Corsica. (July 2016) - Berquier, Cyril; Orsini, Antoine; Ferrat, Lila; Andrei-Ruiz, Marie-Cécile
Abstract: Corsica is a French island in the western Mediterranean with numerous distinct geomorphological, landscape, and biological characteristics. These specific attributes, mostly related to insularity, are hardly taken into account by the biological indices currently recommended in the framework of the European Union Water Framework Directive "WFD" for assessing the ecological status of watercourses. Thus, this work has focused on developing an innovative biological index adapted to the specific context of territories such as Corsica, based on the Odonata group. In this context, imago sampling of Odonata was performed at 40 representative stations to assess the 33 major permanent rivers of the island. In parallel, various biological, hydrological, and physicochemical parameters affecting the ecological status of these organisms were recorded. The data collected on nearly 30 species of Odonata allowed for the accurate description of the typical populations of Corsican watercourses, highlighting this group's potential as a biological indicator. An indicator value was assigned to the 12 species identified as the most representative of these environments. The results were used to develop 5 biological indices based on simple statistical descriptors. The index that was found to be the best for assessing the ecological status of the watercourses, as indicated by correlation tests, was named " Odonata Community Index – Corsica" (OCIC), and was finally confronted with the 5 biological indices recommended by the WFD and currently used in Corsica. The results of this study confirm the significant potential of the OCIC index compared to other "official" indicators, that are limited in they do not accurately assess all territories. The results of our tests indicate that this new index using Odonata group appears to be a credible method that could potentially improve the evaluation system currently used for monitoring the ecological quality of watercourses in Corsica.